Integrasi Kurikulum Pendidikan Nasional Dan Kurikulum Pesantren - Muhammad Akhsanul Muhtadin; Tio Ari Laksono (Universitas Islam Lamongan, 2022)
General education is usually formulated in the form of ideal behavior by the outlook on life and philosophy of a nation which is formulated by the government in the form of laws. Meanwhile, Islamic boarding schools are a subculture that appears in society and changes with the larger world, so Islamic boarding schools become educational institutions that have their characteristics and are different from other educational institutions. With contradictory differences, both are needed to improve the quality of education in Indonesia, so a combination of the national curriculum and the Islamic boarding school curriculum is needed. This study uses the method (literature review) by tracing various references related to the integration of the national education curriculum and the pesantren curriculum. The integration of the national curriculum and the pesantren curriculum has succeeded in making its graduates more competent compared to schools that only use the national curriculum. There are proven indications of the results achieved for the success of the education system desired by the government so that this integration system is needed by future generations.